Disease-free Pre-Basic Seed Potato Production through Tissue Culture in Nepal (Nepal Agriculture Research Journal, 2014)
Pre-basic seed potatoes are disease free potato minitubers produced by transplanting pathogen free in vitro potato plantlets under protected condition in aphid-proof glasshouse  and/or screen house. Double antibody sand witched - enzyme linked immuno-sorbant assay  is used to test six major potato viruses, namely PLRV, PVS, PVX, PVY, PVA and PVM.  Thermotherapy cum meristem tip excision techniques are used to eliminate these viruses.  Virus free in vitro potato plantlets are rapidly propagated by single nodal cuttings on  modified MS media. For pre-basic seed production disease free in vitro potato plantlets are  transplanted in the sterile sand soil substrate under glasshouse and screen house, once in  autumn season and next in spring season. Since 1990, National Potato Research Program has  been producing about 200,000 pre-basic seeds annually. So far, PBS of 19 different  recommended and released potato cultivars has been produced. Till date 3,465,799 PBS had  been produced and 3,217,666 pre-basic seeds distributed to the different seed potato growers  groups, District Agriculture Development Offices, government farms/research stations, and  NGOs/INGOs for subsequent basic seed potato production. After establishment of tissue  culture facilities in National Potato Research Program, the productivity of potato has been  increased by 71% due to utilization of pre-basic seed potatoes.Nepal Agric. Res. J. Vol. 8, 2007, pp. 7-13DOI: http://dx.doi.org/10.3126/narj.v8i0.11564